“ABSOLUTE FRIENDS”: UNITED STATES ESPIONAGE AGAINST GERMANY AND PUBLIC INTERNATIONAL LAW - Terry, Patrick (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional, 2015)
Since 2014, the USA stands accused of engaging in espionage against Germany, a NATO partner and supposedly close ally. Many, though by no means all of these allegations became known because of the Snowden revelations. In Germany, this has led to a public backlash and has caused many to criticize the German government’s feeble reaction. Against this backdrop, this article considers whether the alleged US conduct may have even gone beyond abusing Germany’s trust by actually violating public international law. After summarizing the main accusations, the state of the debate on the legality of espionage in international law will be analysed. This will allow the conclusion that there is so far no convincing answer to the question of whether espionage violates public international law or not. This is due to the imprecise, contradictory and changing definitions of the term “espionage”, but also, more importantly, to the fact that there is no necessity for international law to deal with “espionage”. Rather, customary international law already provides clear guidance as to the lawfulness or unlawfulness of most, if not all, activities commonly associated with espionage. A detailed legal analysis of the alleged US spying activities will confirm this proposition and reveal that US conduct, if proven, did indeed violate public international law in each case. The USA not being able to rely on any legal justification for its actions, Germany would consequently be well within its rights to adopt countermeasures.